The Role of Core Capabilities in Achieving the Entrepreneurial Orientation (NTU journal for Administrative and Human Sciences (JAHS), 2023)
The current study aims to demonstrate the role of core capabilities in achieving the entrepreneurial orientation of the organization, by studying the core capabilities with their dimensions (technology management, empowerment, cooperation, human capital, distinctive capabilities) and showing the impact of these dimensions in achieving the entrepreneurial orientation, and starting from the basic problem Which is represented in the extent of the contribution and role of the dimensions of core capabilities in achieving the entrepreneurial orientation, as this study included the deanship, assistants, heads of departments and teachers in the Administrative Technical College as they were the selectedsample for this study, and through the use of the questionnaire form to know the extent of the existence of this role or not, and thus the study reached a group One of the most important conclusions is that the core capabilities of the organization can be accurately determined through the participation of all its departments and units, and the pioneering approach is an essential element in achieving economic development, due to the expansion and development it allows in business and projects, whether industrial, commercial or service, which drives the development process in countries towards prosperity, In addition to the need for the college administration to care about and embrace distinguished capabilities and work to give the pioneering managers the opportunity to take their leading positions and work to motivate them in order to provide an outstanding service in their field of work.